2019
DOI: 10.1049/iet-gtd.2018.6612
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐dependent load model‐based short‐term distribution network planning considering carbon tax surplus

Abstract: Nowadays, strategies to cope with environmental issues play a crucial role in the development of planning methodologies for electric distribution networks (EDNs). The primary goal of these methodologies is to find the equilibrium point, for which the EDN provides a high-quality service with the most environmentally-committed operation. Based on this fact, an alternative strategic approach for short-term EDN planning is presented in this manuscript. This decision-making scheme is based on classical investment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…When substituting α w in PDF and CDF, the Rayleigh model for WT can be obtained as a function of average wind speed according to the Equations (12) and (13).…”
Section: Photovoltaic System (Pvs)mentioning
confidence: 99%
See 1 more Smart Citation
“…When substituting α w in PDF and CDF, the Rayleigh model for WT can be obtained as a function of average wind speed according to the Equations (12) and (13).…”
Section: Photovoltaic System (Pvs)mentioning
confidence: 99%
“…Bacterial Foraging Optimization Algorithm is used to identify the optimum capacity of the DG and DSTATCOM under different load is presented in [11]. A traditional planning approach for electric distribution networks is studied under Voltage-dependent load mode considering other environmental and economic perspectives in [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers also explored the effects of different taxes on system planning across various time horizons. These studies focused on system expansion planning by considering different tax amounts allocated to carbon reduction in the planning process [24,25]. Additionally, certain articles in this category examined taxes and system planning, taking into account constraints on maximum carbon emissions in the target year [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The works described in [7]- [10] model the load behavior using a constant power representation, as it is more practical and easier to implement. However, several studies on the operation of medium-voltage distribution systems have shown that the behavior of load depends on voltage [12] and that correctly modeling this behavior allows for significant reductions in energy consumption, which may have an important impact on the investment plans [13], [14]. Within this context, the incorporation of investment decisions in voltage control equipment, such as CBs and voltage regulators (VRs), in the DSP model becomes more important.…”
Section: Introductionmentioning
confidence: 99%